2022
DOI: 10.17159/sajs.2022/10383
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and in silico investigations of Sudanese roselle

Abstract: We analysed four different Sudanese roselle samples for their potential as novel xanthine oxidase (XO) inhibitors. Phytochemical screening showed the presence of polyphenols, flavonoids, organic acids, saponins and sterols in all samples. Liquid chromatography with tandem mass spectrometry (LC-MS/ MS) was used to identify and characterise five anthocyanins in all samples: cyanidin-3-glucoside (cy-3-glu), delphinidin-3-sambubioside (dp-3-sam), cyanidin-3-rhamnoside (cy-3-rhm), delphinidin-3‑rhamnoside (dp-3-rhm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Black rice anthocyanins decreased the proportion of β‐turns and random coil in XO, limited the binding and catalysis of the substrate with XO, and thus, reduced the XO activity. The anthocyanins in S. roselle were mainly glycosylated cyanidin and delphinidin, which interact with XO through hydrogen bonds, hydrophobic interactions, and/or electrostatic repulsions (El‐Naeem et al., 2022). Among them, delphinidin‐3‐rhamnoside was the most active substance.…”
Section: Mechanism Of Xo Activity and Hua Inhibition By Flavonoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Black rice anthocyanins decreased the proportion of β‐turns and random coil in XO, limited the binding and catalysis of the substrate with XO, and thus, reduced the XO activity. The anthocyanins in S. roselle were mainly glycosylated cyanidin and delphinidin, which interact with XO through hydrogen bonds, hydrophobic interactions, and/or electrostatic repulsions (El‐Naeem et al., 2022). Among them, delphinidin‐3‐rhamnoside was the most active substance.…”
Section: Mechanism Of Xo Activity and Hua Inhibition By Flavonoidsmentioning
confidence: 99%
“…Among them, delphinidin‐3‐rhamnoside was the most active substance. Its main binding sites to XO were Thr354 and Arg394 (via hydrogen bonds), and the binding energy of delphinidin‐3‐rhamnoside was −10.9 kcal/mol, which was lower than that of topiroxostat (a standard drug for the treatment of HUA) with −8.6 kcal/mol (El‐Naeem et al., 2022). The findings suggest that anthocyanins are potential drugs for the treatment of HUA.…”
Section: Mechanism Of Xo Activity and Hua Inhibition By Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic acids like neochlorogenic acid and chlorogenic acid, in addition to organic acids such as hydroxycitric acid, hibiscus acid, and hibiscus acid hydroxyethyl ester were also identified. Few phytochemical studies were conducted on the white calyx, and phytochemical screening showed that polyphenols, flavonoids, organic acids, sterols, and saponins were detected . Pharmacologically, H.…”
Section: Introductionmentioning
confidence: 99%
“…sabdariffa and it is frequently consumed as a hot or cold beverage and used in traditional medicine, there has been limited systematic study on the efficiency of different solvent extractions on bioactive molecules. Moreover, there are few studies on the chemical and biological activities of white roselle (WR) variety. , In this context, the present study was designed to investigate the chemical profiles, antioxidant activity, and enzyme inhibition property of extracts from red roselle (RR) and WR varieties obtained through maceration, infusion, and decoction by using water and methanol as extraction solvents.…”
Section: Introductionmentioning
confidence: 99%